Diffusing education technology: A model for language teacher professional development in CALL. (November 2018) - El Shaban, Abir; Egbert, Joy
Abstract: This conceptual paper adapts Rogers' Diffusion of Innovations Theory (DIT; Rogers, 1995/2003), integrating it with the teacher technology education literature, in order to provide a model for professional development in computer-assisted language learning (CALL). The model consists of two stages that teacher educators can consider when developing and providing CALL professional development for teachers. Each stage was designed to address key issues in the literature. In Stage 1, persuasion, knowledge, and practice are the key issues addressed. Stage 2 focuses on providing an enabling environment for teacher growth. After presenting the literature that grounds the model, this paper describes an example of the strategies in use. The goal is to guide teacher educators to think about effective CALL professional development and to help address teachers' resistance toward adopting CALL technologies.